A comparative study of Cu–Ni Alloy using LIBS, LA-TOF, EDX, and XRF. (28th November 2016) - Ahmed, N.; Ahmed, R.; Rafiqe, M.; Baig, M.A.
Abstract: LASER induced breakdown spectroscopy (LIBS) has been used for the quantitative analysis of Cu–Ni alloy of known composition (75% Cu, 25% Ni) using the one line calibration free-LIBS (OLCF-LIBS), self-calibration-LIBS (SC-LIBS), calibration free LIBS (CF-LIBS), time of flight-mass spectroscopy (TOF-MS), energy dispersive X-ray spectroscopy (EDX) and X-ray fluorescence spectroscopy (XRF). For the LIBS-based studies, the plasma was generated by focusing the beam of a Q-switched Nd:YAG laser (532 nm, pulse energy about 200 mJ, 5 ns pulse duration) while the sample was placed in air at an atmospheric pressure. Plasma temperature about (9500 ± 300) K was calculated by the Boltzmann plot method using the neutral lines of Cu and Ni whereas the electron number density was calculated (2.0 ± 0.5) × 10 16 cm −3 from the Stark broadening of an isolated Cu line as well as using the relative intensities of the neutral and singly ionized optically thin lines in the Saha–Boltzmann equation. The elemental compositions determined by different LIBS methods and standard techniques are; OLCF-LIBS (69% Cu and 31% Ni), SC-LIBS (72% Cu and 28% Ni), CF-LIBS (74% Cu and 26% Ni), TOF (74% Cu and 26% Ni), EDX (75% Cu and 24.5% Ni), XRF (73% Cu and 24.7% Ni), and LA-TOF (74% Cu and 26% Ni). It is demonstrated that the CF-LIBS method gives compositions comparable with that determined by LA-TOF, EDX, or XRF, which is also in agreement with the certified reported composition.